Building a Culture of Compliance: The Influence of Tax Socialization and Inclusion on Indonesian Micro, Small, and Medium Enterprises (MSMEs) Taxpayers - Putra, Danang Adi; Nila Aprila; Pratana Puspa Midiastuty; Herawansyah (HM Publisher, 2024)
Taxes serve as the cornerstone of any nation's economic framework, functioning as both a regulatory mechanism and a primary source of government revenue. They are indispensable for managing taxpayer behavior, ensuring a steady stream of state income, and financing essential public services and infrastructure development. In Indonesia, the compliance of micro, small, and medium enterprises (MSMEs) is pivotal to the nation's fiscal well-being. This study delves into the factors that influence MSME taxpayer compliance, specifically focusing on the role of tax socialization, tax inclusion, and the involvement of tax volunteers. A quantitative research approach was adopted, involving the distribution of questionnaires to MSME taxpayers in Indonesia. The data collected was then analyzed using SPSS software to test the hypotheses regarding the impact of tax socialization, tax inclusion, and tax volunteers on taxpayer compliance. The findings of this study reveal that tax socialization and tax inclusion positively influence the level of tax compliance among Indonesian MSME taxpayers. Furthermore, the involvement of tax volunteers also has a positive impact on enhancing taxpayer compliance. This study underscores the importance of tax socialization and tax inclusion in fostering a culture of compliance among MSMEs in Indonesia. The positive role of tax volunteers in assisting taxpayers and promoting compliance is also highlighted. These findings have significant implications for tax authorities in their efforts to improve tax compliance rates and enhance revenue collection.